2007
DOI: 10.18474/0749-8004-42.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Deterrency and Toxicity of Essential Oils to Argentine and Red Imported Fire Ants (Hymenoptera: Formicidae)

Abstract: Laboratory assays were conducted to evaluate deterrency and contact toxicity of six essential oils to the Argentine ant, Linepithema humile (Mayr), and the red imported fire ant, Solenopsis invicta Buren. In choice tests, both Argentine ants and fire ants crossed barriers treated with multiple rates of basil, citronella, lemon, peppermint, or tea tree oil less frequently than paired control barriers. Eucalyptus oil did not prevent movement of either species at any of the rates tested. In continuous exposure as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Mint oil granules were proven to be toxic and repel-lent to red imported fire ants, and all red imported fire ant mounds that were treated with mint oil granules were abandoned (Appel et al, 2004). Citronella oil was repellent and toxic to both Argentine and red imported fire ants (Wiltz et al, 2007). The essential oil from Cinnamomum osmophloeum Kaneh.…”
mentioning
confidence: 99%
“…Mint oil granules were proven to be toxic and repel-lent to red imported fire ants, and all red imported fire ant mounds that were treated with mint oil granules were abandoned (Appel et al, 2004). Citronella oil was repellent and toxic to both Argentine and red imported fire ants (Wiltz et al, 2007). The essential oil from Cinnamomum osmophloeum Kaneh.…”
mentioning
confidence: 99%
“…Monoterpenoids such as 1,8-cineole, anisole, limonene, and -pinene showed vapor activity against eggs and adult P. humanus capitis . Deposits of basil, citronella, lemon, peppermint, and tea tree oils were not highly toxic to Argentine ants, Linepithema humile (Mayr), and red imported fire ants, Solenopsis invicta Buren, but deterred them from crossing barriers (Wiltz et al, 2007). Only citronella oil provided 50% kill of Argentine ants in 34 min and 100% kill within 24 h.…”
Section: Nonresidual Insecticidesmentioning
confidence: 91%
“…Over time, they removed thousands of workers, a substantial quantity of brood, and numerous queens from the outdoor environment. In the absence of water sources, small cohorts of Argentine ant workers quickly moved into small Petri dishes containing moistened Castone [ 42 , 43 ], and Schilman et al [ 38 ] showed that Argentine ants, when given a choice, were attracted to and harbored in small cups where the relative humidity was >90%. For decades, Argentine ant researchers have routinely taken advantage of the Argentine ant’s susceptibility to desiccation when separating recently collected ants from the field from their leaf litter debris.…”
Section: Alternative Methods Of Ant Controlmentioning
confidence: 99%
“…Over time, they removed thousands of workers, a substantial quantity of brood, and numerous queens from the outdoor environment. In the absence of water sources, small cohorts of Argentine ant workers quickly moved into small Petri dishes containing moistened Castone [42,43], and Schilman et al [38] showed that Argentine ants, when given a choice, were attracted to and harbored in small cups where the relative [37]. In this image, on a cool October evening in Georgia, Argentine ants located and recruited to a warm computer battery charger located indoors, where grams of brood were relocated (photo, D. Suiter).…”
Section: Figurementioning
confidence: 99%